Alignment of silver nanowires with controlled density and distance - Ong, Isabelle Min Yee (Nanyang Technological University, 2020)
In recent years, the development of one-dimensional nanomaterials has been progressing at a great pace. Researchers have focussed on the anisotropic physical properties of these materials – nanorods, nanoparticles, nanotubes – for applications into all opto-electronics. Among these materials, Silver nanowires (AgNWs) have been widely studied among researchers for its properties of optical transmittance, along with high aspect ratios and high intrinsic conductivity. Therefore, several methods of assembly techniques of AgNWs have been reported. Where techniques like dip coating and electrostatic spraying produce randomly orientated AgNWs have been discovered, in-plane assembly techniques are highly valued in opto-electronics due to its conductivity, transparency and stretchable qualities, as the AgNWs are aligned in a single direction. In this report, a novel method of stirring-assisted assembly of aligned AgNWs is studied further. Using this technique, a monolayer of AgNWs and a layer of polyethyleneimine (PEI) is formed onto both polydimethylsiloxane (PDMS) substrate and glass slide, and compared. The AgNWs are aligned using a facile stirring technique, producing alignment within ±0.5° of the stirring direction. Herein, glass material for this stirring technique was found to be a poor substrate for this technique of alignment of AgNWs, owing to factors involving PEI, interactions of PEI with glass, the washing of PEI from glass, with other possibilities, is discussed. Overall, 500 rpm stirring was used for the experiments, with stirring duration of 30 minutes. The usage of PEI as an adhesive for AgNWs on glass, was found to be problematic, and hindered proper alignment of the AgNWs on the substrate.